2023
DOI: 10.1021/acs.est.2c07016
|View full text |Cite
|
Sign up to set email alerts
|

A Flow-through Passive Sampler for Microplastics in Air

Abstract: Microplastics (MP) in air have attracted increasing attention because of their ubiquitous presence. Accurate atmospheric concentrations of MP are essential for evaluating their capacity for long-range transport and for assessing human inhalation risk. In order to sample airborne MP in locations with limited power supply, we adapted a flow-through passive sampler by placing a glass fiber filter in the inner sampling tube. To test the new sampler’s performance under field conditions, two sizes of the flow-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Only a few studies reported atmospheric deposition of microplastics in the Tibetan Plateau, with fluxes of 5.8-52 items/m 2 /d at the Nam Co basin and 21-26 items/m 2 /d at the Demula glacier [20,77]. Another study reported very low airborne microplastic concentrations of 0.15-0.25 items/m 3 during testing of a flow-through passive sampler in a suburb of Lhasa city [21].…”
Section: Snow/ice and Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies reported atmospheric deposition of microplastics in the Tibetan Plateau, with fluxes of 5.8-52 items/m 2 /d at the Nam Co basin and 21-26 items/m 2 /d at the Demula glacier [20,77]. Another study reported very low airborne microplastic concentrations of 0.15-0.25 items/m 3 during testing of a flow-through passive sampler in a suburb of Lhasa city [21].…”
Section: Snow/ice and Atmospherementioning
confidence: 99%
“…The shape and color of microplastics in snow/ice were typically fibrous and colorful (e.g., black, blue and red) (Table S4). Both the atmospheric deposited samples collected from the Nam Co basin and airborne samples collected from the Lhasa suburb were dominated by transparent, small size and fibrous microplastics [20,21]. The dominant polymer types of snow/ice, atmospheric deposition and airborne microplastics were highly variable, including PET, PP, PE and cellophane.…”
Section: Snow/ice and Atmospherementioning
confidence: 99%
“…However, spinel oxide catalysts still face the disadvantages of high lattice oxygen activation temperatures and low specific surface area. 7 Thus, the preparation of spinel oxides with high specific surface area is an efficient approach to improving catalytic performance.…”
mentioning
confidence: 99%